Prosodic Analysis of English Utterances in Student with Attention Deficit Hyperactivity Disorder in the Context of Riddle Game - Amal, Rizal Alamsa; Hariri, Tatang (ELT Worldwide: Journal of English Language Teaching, 2025)
This study focuses on prosodic patterns, specifically intonation and stress, in student with attention deficit hyperactivity disorder (ADHD) during riddle game situations. The main objective of this research is to identify and analyze how ADHD and other factors influence prosodic patterns in English speech as a second language in a gaming context. The data source comes from an 11-year-old ADHD student with the initials D, who studies at Corner Stone School in Makassar. Data collection was conducted using an observation technique. Observations were carried out while playing a riddle game, with audio recordings used for analysis. The results indicate a tendency to emphasize the beginning of utterances, such as the words "Faster," "Help," and "Yes," which function as signals for the listener to focus on the core message. Additionally, the intonation pattern showed a tendency to use falling intonation, characterized by a high pitch at the beginning of the utterance and a lower pitch at the end. Interestingly, the prosodic patterns produced by the ADHD student in this study were not significantly different from those of non-ADHD students. This research suggests that although students with ADHD face challenges in attention and impulse control, the subject in this study could still adjust their prosodic patterns to convey messages effectively in specific contexts, such as in a riddle game setting.